Relationship between Knowledge Level and Cadre Attitudes About the Independent Care Program for the Use of Acupressure - Arya Brain Agustian; Dwi Linna Suswardany (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Traditional health services that have been provided by health service facilities have an important purpose in highlighting disease problems in society, but public awareness in implementing independent care does not yet exist. Therefore, this research aims to determine the relationship between the level of knowledge and attitudes of cadres towards the self-care program using acupressure. The method used in this research is quantitative with a cross-sectional approach. This research was carried out in the working area of the Kartasura Community Health Center, namely in Ngadirejo Village and Pucangan Village in February 2024 with a population of 159 people. This study used non-probability sampling with a total sampling technique with a total of 159 respondents in accordance with inclusion and exclusion. Data collection was carried out using a questionnaire which was filled out directly by the respondent. The questionnaire has gone through validity and reliability tests before being used. The data analysis used in this research is descriptive analysis in the form of frequency distribution and chi-square test. Data analysis was carried out using the SPSS application. The chi-square test shows that there is a significant relationship between cadre knowledge and cadre attitudes towards the self-care program using acupressure in the Kartasura Health Center working area, especially Ngadirejo Village and Kartasura Village with a p-value of 0.031 < α 0.05. The conclusion is that the average cadre has a good level of knowledge and attitude towards the self-care program using acupressure. So with this program researchers have succeeded in increasing cadres' understanding of the acupressure method as part of independent care to increase knowledge of the benefits of acupressure in reducing disease problems in the community. Suggestions for cadres who have poor knowledge scores are that they can increase their knowledge scores by diligently participating in training held by the Kartasura Community Health Center. Keywords : Acupressure, Education, Attitude